The Extent of Homogeneity in the Distribution of Petrophysical Properties that Affecting the Primary and Enhanced Oil Recoveries of Reservoir Rocks in Zubair Formation of South Iraq (Baghdad Science Journal, 2025)
Records of two regionalized variables were processed for each of porosity and permeability of reservoir rocks in Zubair Formation (Zb-109) south Iraq as an indication of the most important reservoir property which is the homogeneity,considering their important results in criterion most needed for primary and enhanced oil reservoirs.The results of dispersion treatment,the statistical incorporeal indications,boxes plots,rhombus style and tangents angles of intersected circles indicated by confidence interval of porosity and permeability data, have shown that the reservoir rocks of Zubair units (LS),(1L) and (DJ) have reservoir properties of high quality,in contrast to that of Zubair units (MS) and (AB)which have reservoir properties of less quality than the rest.In addition,the co- efficient of the central tendency of permeability data for the reservoir rocks have indicated the homogeneity,systematic and normal distribution, in contrast to porosity data of (DJ) & (AB) units that follow a distribution which predominate in difference and heterogeneity in their values.